The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1017/s0021859607007113
|View full text |Cite
|
Sign up to set email alerts
|

Influence of short-term Leucaena leucocephala feeding on milk yield and its composition, thyroid hormones, enzyme activity, and secretion of mimosine and its metabolites in milk of cattle

Abstract: SU MMARYFour Karan/Friesian crossbred (HolsteinrTharparkar) dairy cows in late lactation (>200 days) were fed a basic diet of green maize and concentrates with an increasing proportion of Leucaena leucocephala (leucaena) leaf meal (LLM). The proportion was gradually increased from 0 . 25 of the dry matter intake (DMI) in the first week to 0 . 50 in the second, 0 . 75 in the third and ad libitum in the fourth week. Mimosine, 3,4-dihydroxy pyridine (3,4-DHP) and 2,3-dihydroxy pyridone (2,3-DHP) levels were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 16 publications
(32 reference statements)
2
7
0
2
Order By: Relevance
“…This agrees with Ghosh et al (2007), who reported intakes of up to 50 % Leucaena in cows without signs of toxicity. Plasma mimosine levels observed in the present study (1270-1530 μg/mL) were far higher than those reported by Ghosh et al (2007) in confined cows (25 and 71 μg/mL).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This agrees with Ghosh et al (2007), who reported intakes of up to 50 % Leucaena in cows without signs of toxicity. Plasma mimosine levels observed in the present study (1270-1530 μg/mL) were far higher than those reported by Ghosh et al (2007) in confined cows (25 and 71 μg/mL).…”
Section: Discussionsupporting
confidence: 92%
“…This agrees with Ghosh et al (2007), who reported intakes of up to 50 % Leucaena in cows without signs of toxicity. Plasma mimosine levels observed in the present study (1270-1530 μg/mL) were far higher than those reported by Ghosh et al (2007) in confined cows (25 and 71 μg/mL). This difference may be explained by the high rumen degradability of L. leucocephala (Miranda et al 2012), especially when ruminants are grazing and thus allowed to select their diet.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, many of these forage trees have not been widely used because they often contain antinutritional compounds that have deleterious effects on animal yield [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple purpose trees, such as leucaena (Leucaena leucocephala), have proven to be effective by improving nutrient utilisation, leading to improving nutrient intakes (Majuva-Masafu and Linington 2006), nutrient digestibility and animal performance (Rubanza et al 2005) and lactation (Ghosh et al 2007) and also reduce the use of expensive concentrates (Jetana et al 2011). The farmers who raise buffaloes are not motivated to use this plant.…”
Section: Introductionmentioning
confidence: 99%